2021
DOI: 10.1002/smll.202100762
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Electron Transfer from Electron‐Sponge Polyoxometalate to Single‐Metal Site Metal–Organic Frameworks for Highly Selective Electroreduction of Carbon Dioxide

Abstract: The ORCID identification number(s) for the author(s) of this article can be found under https://doi.org/10.1002/smll.202100762. conversion are potential methods to lower CO 2 concentration in the atmosphere. [2][3][4] In contrast to CO 2 capture, CO 2 conversion is more promising, as it can convert CO 2 into low-carbon fuels or other valuable chemicals such as CO, CH 4 , HCOOH, and C 2 H 5 OH. [5][6][7][8] Importantly, for industrial applications, CO 2 reduction reaction (CO 2 RR) is considered to be a practic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 59 publications
(48 reference statements)
0
39
0
Order By: Relevance
“…Cysteine is one of the most reactive amino acids in nature, and its thiol side chain could be moderately oxidized into disulfide linkage, which plays a vital role in stabilizing the folding structures of proteins. , The incorporating of cysteine into peptide coacervates may enable the artificial system to be cured via an ingenious choice of oxidants. It has been known that POMs are a kind of oxidative polyanions with monodispersed size, well-defined topology, chemical diversity, and bioacitvity. In particular, molybdenum- or vanadium-substituted POMs have the capacity to oxidize the cysteine into cystine at room temperature. , These versatile properties of POMs fascinated us, who are intrigued with the idea of regulating the coacervation of cysteine-containing peptide segments and their subsequent curing under the water line. In the present study, we designed and synthesized two kinds of redox-complementary peptide/POM coacervates.…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine is one of the most reactive amino acids in nature, and its thiol side chain could be moderately oxidized into disulfide linkage, which plays a vital role in stabilizing the folding structures of proteins. , The incorporating of cysteine into peptide coacervates may enable the artificial system to be cured via an ingenious choice of oxidants. It has been known that POMs are a kind of oxidative polyanions with monodispersed size, well-defined topology, chemical diversity, and bioacitvity. In particular, molybdenum- or vanadium-substituted POMs have the capacity to oxidize the cysteine into cystine at room temperature. , These versatile properties of POMs fascinated us, who are intrigued with the idea of regulating the coacervation of cysteine-containing peptide segments and their subsequent curing under the water line. In the present study, we designed and synthesized two kinds of redox-complementary peptide/POM coacervates.…”
Section: Introductionmentioning
confidence: 99%
“…The transportation of electrons can be facilitated by incorporating POMs into MOFs channels and finally the performance of the active site can be improved. For example, Lan and coworkers [ 134 ] reported POM@PCN‐222(Co) composite by combining the electron rich structure of POM and high surface area of MOF ( Figure ). As expected, the electron transfer property of composite material was considerably improved and a particular composite named H‐POM@PCN‐222(Co) showed better CO 2 RR performance with 96.2% FE CO at −0.8 V versus RHE and stability of 10 h. Further, DFT calculations revealed that Co single sites in PCN‐222(Co) were improved by directional electron transfer in the composite and reduced the energy barrier for the rate‐determining step.…”
Section: Functionalization Of Mofs For Co2rrmentioning
confidence: 99%
“…28–30 With respect to inorganic materials, light absorption of meta-free photocatalyst can be readily optimized by rational design of the molecular structure. 31–33 In addition, metal-free photocatalysts are favoured to proceed one-electron process, while two-electron process is avoided for hydrogen evolution reaction as shown in eqn (3). 34 2H + + 2e − → H 2 (−0 V vs. NHE)…”
Section: Introductionmentioning
confidence: 99%